2016
DOI: 10.17795/soj-8568
|View full text |Cite
|
Sign up to set email alerts
|

Role of Body Exhaust System in Reducing Peri-Prosthetic Joint Infection, Literature Review

Abstract: Context: There is a need to determine if body exhaust suits which were initially used and recommended by Sir John Charnley has a role in minimizing bacterial shedding in the operating room. Evidence Acquisition: The English literature search conducted for relevant articles. 14 articles were relevant to the role of body exhaust system in total joint replacement. Results: There is controversial evidences regarding the role of body exhaust system in reducing pei-prosthetic joint infection but most evidences agree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…7,8 Moreover, some studies have suggested that SHS only protects surgeons and other scrubbed personnel from potential fluid and bloodborne transmissions, 9 but does not reduce the incidence of surgical field contaminations. [10][11][12][13][14] As a result, the effectiveness of SHS in reducing the risk of surgeon-derived contamination and PJI has been questioned.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Moreover, some studies have suggested that SHS only protects surgeons and other scrubbed personnel from potential fluid and bloodborne transmissions, 9 but does not reduce the incidence of surgical field contaminations. [10][11][12][13][14] As a result, the effectiveness of SHS in reducing the risk of surgeon-derived contamination and PJI has been questioned.…”
Section: Introductionmentioning
confidence: 99%